1984
DOI: 10.2307/2399035
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Lower Cretaceous Angiosperm Pollen and the Origin and Early Evolution of Flowering Plants

Abstract: In the last decade significant new information has been gained about the early evolution of flowering plants through studies of Early Cretaceous angiosperm pollen and the pollen of living primitive flowenng plants. Although most recent palynological studies of extant primitive angiosperms have used both scanning and transmission electron microscopy, few ultrastructural studies of early fossil aneioSDerm nollen erains pvict Thic r.an»r â"¢r^ro,o^«to « * * i.. ^li. _-^.._^.-tu:-* Cretaceous angiosperm Frederi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
183
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 236 publications
(198 citation statements)
references
References 1 publication
9
183
0
1
Order By: Relevance
“…This is similar to but larger and more coarsely columellar than Zone I and II pollen compared to Clavatipollenites hughesii (Doyle et al 1975;Walker & Walker 1984), which also occurs in our samples (Plate 3, figure 2). Heimhofer et al (2007) reported similar pollen, as Clavatipollenites cf.…”
Section: Correlation Of the Glen Rose Samples With The Potomac Group supporting
confidence: 85%
See 2 more Smart Citations
“…This is similar to but larger and more coarsely columellar than Zone I and II pollen compared to Clavatipollenites hughesii (Doyle et al 1975;Walker & Walker 1984), which also occurs in our samples (Plate 3, figure 2). Heimhofer et al (2007) reported similar pollen, as Clavatipollenites cf.…”
Section: Correlation Of the Glen Rose Samples With The Potomac Group supporting
confidence: 85%
“…The boundary between Zones I and II was based primarily on the appearance of new species of spores and the first tricolpate angiosperm (eudicot) pollen. In Zone I Brenner reported reticulate-columellar monosulcates, including Clavatipollenites, which was first described from the Barremian of England (Couper 1958 considered such forms incertae sedis, but their angiospermous affinities were subsequently confirmed by studies of exine structure (Doyle et al 1975;Walker & Walker 1984) and association with angiosperm stamens and carpels Friis et al 1999Friis et al , 2011. Based on the data available then from other areas, he dated Zone I as Barremian or Aptian and Zone II as Albian.…”
Section: Background On the Potomac And Portuguese Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Crassidenticulum decun-ens shows close similarities to extant Chloranthaceae (considered one of the primitive families of Laurales by Takhtajan [1980]), although its precise combination of venational features is not known from any extant genus. This is not surprising, because dispersed pollen and flowers comparable to extant genera of Chloranthaceae occur in older rocks (Walker and Walker, 1984;Friis and others, 1986). Landonia provides a possible evolutionary link between extant primitive Laurales that produce inaperturate pollen (Amborellaceae and Monimiaceae) and more derived members of the alliance because it combines (1) the pinnate venation and generally isodiametric intercostal regions characteristic of Amborellaceae and Monimiaceae, and (2) the generally transverse and sparsely branched intercostal tertiary venation with admedial branches characteristic of Gomortegaceae and certain Hernandiaceae (Illigera).…”
Section: Evolutionary Considerationsmentioning
confidence: 88%
“…During this time, the angiosperms began their adaptive radiation, and major extant lineages at the level of subclass, order, and family made their first appearance. (See, for example, Wolfe and others, 1975;Hickey and Doyle, 1977;Dilcher, 1979;Upchurch, 1984;Walker and Walker, 1984. ) Associated with this adaptive radiation were progressive and broad-scale ecological displacements, wherein cycadophytes, ginkgophytes, and other dominant groups of gymnosperms declined in relative abundance and diversity and were replaced in most habitats and geographic regions by angiosperms, especially at lower and middle paleolatitudes (Doyle and Hickey, 1976;Hickey and Doyle, 1977;Retallack andDilcher, 1981, 1985;Crane, 1987;Upchurch and Wolfe, 1987b).…”
Section: Introductionmentioning
confidence: 99%